Approaches to the World The Multiple Dimensions of the Social - Lindemann, Gesa (Nomos Verlagsgesellschaft mbH & Co. KG, 2021)
Responding to the critique of methodological ethnocentrism, Lindemann develops a new general social theory that is also highly sensitive to socio-cultural differences. Drawing on Helmuth Plessner's theory of excentric positionality, social order is understood as a symbolically and technically mediated spatio-temporal order that is integrated by an order of violence. Lindemann hereby brings together three significant aspects of recent debates: the debates on the necessity of a theoretical turn (such as the linguistic turn, the material turn, the body turn, the pictorial turn and the spatial turn); second, the debates on the actor status of non-humans and the borders of the social world, and third, the discussions about the role of violence in structuring social processes. Als Antwort auf die Kritik des methodologischen Ethnozentrismus entwickelt Lindemann eine neue allgemeinen Sozialtheorie, die sozio-kulturelle Differenzen detailliert zu analysieren vermag. Soziale Ordnung wird dabei als eine symbolisch vermittelte, raum-zeitlich verfasste Ordnung verstanden, die durch eine Ordnung der Gewalt integriert wird. Mit diesem Ansatz verbindet Lindemann drei relevante Diskursstränge der letzten Jahrzehnten: Erstens, die Debatten um die Notwendigkeit theoretischer Neuorientierungen, wie den linguistic turn, den body und spatial turn usw., zweitens, die Debatten um den Status nichtmenschlicher Akteure bzw. um die Grenzen der Sozialwelt sowie drittens, die Debatten um die Bedeutung von Gewalt für soziale Ordnungsbildung.